Meningkatkan Kemampuan Motorik Halus Pada Anak Usia Dini Melalui Permainan Trackball Di Kelompok A RA PERSIS 55 Pangatikan Kabupaten Garut - Widari, Ida; Fauziah, Nadiah Hapsah (LP2M STAI Al-Musaddadiyah Garut, 2024)
This title was raised by researchers based on the results of initial observations of children's fine motor skills in group A RA PERSIS 55 pangatikan Garut which are still not well developed. Among these problems is that children still have difficulty controlling their fine muscles such as not being able to hold a pencil, make lines or circles and the child's hand is still very stiff when flicked. The purpose of this study was to determine the effectiveness of trackball games in improving children's fine motor skills in group A RA exactly 55 pangatikan Garut district. This research uses the type of Classroom Action Research (PTK) with a qualitative approach. The object of this research is the increase in fine motor skills of early childhood in group A1 RA PERSIS 55 Pangatikan Garut Regency, with a total of 10 children. The results of data analysis show that the trackball game on development. Fine Motoric in group A1 RA PERSIS 55 Pangatikan Garut Regency. showed a significant impact related to the fine motor development of female students, seen from the percentage results showing the final value of BB 0%, MB 0%, BSH 20% and BSB 80% of these results were obtained after passing the pre-action, cycle I and cycle II. Keywords: Fine Motoric, Trackball Game, Children